Competition policy's role in network industries: Regulation and deregulation in Estonia - Diana Eerma; Jüri Sepp (OrdnungsPolitisches Portal (OPO), 2007)
The article analyzes the competition policy's role in network industries (energy, telecommunication and railway sector) from points of view regulation and deregulation and institutional aspects of the competition policy in Estonia taking into account the particular developments in some transition countries and practices, which seem to be relevant for further regulating developments in Estonia. The main objective of the article is to find out, what type of institutional arrangement is suitable for regulating network industries in Estonia. Under the observation are institutional and organizational aspects of competition in abovementioned sectors. The article has two parts: First part focuses on particular law, which regulates network industries in Estonia; the second part analyzes institutional and organizational aspects of regulation and competition policy. Considering possibilities for regulation in network industries there are analyzed three different models: single sector-specific regulators and competition board; integrated multi-sector regulatory institution and separate competition board; and unitary competition supervisory and regulatory institution.
Keywords: 330; Estonia; competition policy network industries